Analgesic Use in Older Adults with Back Pain: The BACE Study. Issue 10 (4th August 2014) - Enthoven, Wendy T. M.; Scheele, Jantine; Bierma‐Zeinstra, Sita M. A.; Bueving, Herman J.; Bohnen, Arthur M.; Peul, Wilco C.; van Tulder, Maurits W.; Berger, Marjolein Y.; Koes, Bart W.; Luijsterburg, Pim A. J.
Abstract Background Older patients with back pain are more likely to visit their general practitioner (GP) and are more likely to be prescribed analgesics. Objective To assess analgesic use in older adults with back pain in general practice. Methods The BACE study in the Netherlands is a prospective cohort study. Patients (aged >55 years) with back complaints were recruited when consulting their GP or shortly thereafter. Measurements took place at baseline and at 3‐ and 6‐month follow‐up. For medication use, patients were asked if they had used any medication for their back pain in the previous 3 months and, if so, to specify the medication name, dosage used, frequency of usage, and whether the medication was prescribed or purchased over the counter. Results Of the 1, 402 patients who were approached to enter the study, 675 were included. Of these patients, 484 (72%) reported medication use at baseline. Nonsteroidal anti‐inflammatory drugs (NSAIDs) (57%) were more often used than paracetamol (49%). Paracetamol was mostly obtained over the counter (69%), and NSAIDs were mostly obtained by prescription (85%). At baseline, patients with severe pain (numerical rating scale score ≥7) used more paracetamol, opioids, and muscle relaxants. Patients with chronic pain (back pain >3 months) used more paracetamol, while patients with a shorter duration of pain used more NSAIDs. During follow‐up there was an overall decline in medication use; however, at 3‐ and 6‐month follow‐up, 36% and 30% of the patients, respectively, still used analgesics. Conclusions In these older adults consulting their GP with back pain, 72% used analgesics at baseline. Despite a decrease in medication use during follow‐up, at 3 and 6 months a considerable proportion still used analgesics.